An eco-compatible pathway to the synthesis of mono and bis-multisubstituted imidazoles over novel reusable ionic liquids: an efficient and green sonochemical process. Issue 29 (3rd May 2018) - Ahmed Arafa, Wael Abdelgayed
Abstract : Novel and environmentally benign ionic liquids are synthesized and used as robust catalysts for a sonochemical one pot multi-component synthetic route to functionalized annulated imidazoles in water with excellent yields. Abstract : Novel and environmentally benign ionic liquids (ILs) comprised of DABCO were successfully synthesized. These ILs were used as robust catalysts for the sonochemical one pot multi-component synthetic route for the functionalized annulated imidazoles in water with excellent yields. The present protocol scored well in terms of yield economy as compared with the conventional procedures. The merits of the current green method include simplicity, applicability, broad functional groups tolerance, clean reaction profiles, and no tedious work-up and they give high-to-quantitative yields. From the environmental viewpoint, these eco-friendly green catalysts can be effortlessly retrieved and reused at least seven successive times without substantial loss in catalytic activity.